Photogrammetry-Integrated System Information Modeling (SIM) for Effective Information Access in Construction of Power, Control and ICT Systems - Wang, Ying; Wang, Xiangyu; Hou, Lei; Maynard, Nicoleta (Doboku Gakkai, 2013)
For effective information access to Power, Control and Information and communications technology (ICT) Systems, Systems Information Modeling (SIM) system and photogrammetry technology are employed. This paper aims to investigate the innovative and novel seamless and real-time integration between photogrammetry approach and SIM system. Framework of employing SIM and Photogrammetry for Power, Control and ICT systems is illustrated. A pilot study is designed to rigorously investigate algorithms, approaches, and system architecture to automatically integrate SIM with photogrametry-based interactive virtual environments for efficient and seamless information access to retrieval. This approach is tested and evaluated in several defined trial scenarios where information access is most critical. The strategies, recommendations, and regulations of implanting photogrammetry-based SIM system in existing practice process are developed from the knowledge created through the pilot testing aforementioned. It is proved that the industrial partner can benefit by obtaining a better/best practice solution to their current state of the art.